Algorithmic Capitalism and the Digital Divide in Sub-Saharan Africa. Issue 4 (December 2019) - Karar, Haytham
Digitalization generates new opportunities for employment and earnings, but also entails a plethora of uncertainties and challenges. This article highlights the implications of algorithmic capitalism and how it relates to the digital divide in sub-Saharan Africa by discussing specific examples (Ghana and Kenya), considering the existing structure of social inequality. Both case studies refute the World Bank's argument that economic liberalization and deregulation are sufficient approaches to improve material access to Internet services in the Global South. The article concludes that the digital divide is an extension of the global phenomenon of inequality. Although algorithmic capitalism has increased the number of Internet users in the region, it has failed to bridge the digital divide, particularly the urban–rural division. This article also suggests that privately owned mobile phone service providers can contribute to Internet usage and to bridging the digital divide in sub-Saharan Africa.